New insight into the granule formation in the reactor for enhanced biological phosphorus removal - Pelevina, Anna; Gruzdev, Evgeny; Berestovskaya, Yulia; Dorofeev, Alexander; Nikolaev, Yury; Kallistova, Anna; Beletsky, Alexey; Ravin, Nikolai; Pimenov, Nikolai; Mardanov, Andrey (Frontiers in Microbiology, 2023)
While granulated activated sludge exhibits high productivity, the processes of granule formation are incompletely studied. The processes of granule formation and succession of communities were investigated in a laboratory sequencing batch reactor (SBR) under conditions for enhanced biological phosphorus removal (EBPR) using microbiological and molecular techniques. Active consumption of acetate, primarily by the phosphate-accumulating organisms (PAO), commenced at day 150 of cultivation. This was indicated by the high ratio of molar P-released/acetate uptake (0.73–0.77 P-mol/C-mol), characteristic of PAO. During this period, two types of granule-like aggregates formed spontaneously out of the activated sludge flocs. The aggregates differed in morphology and microbial taxonomic composition. While both aggregate types contained phosphorus-enriched bacterial cells, PAO prevailed in those of morphotype I, and glycogen-accumulating organisms (GAOs) were predominant in the aggregates of morphotype II. After 250 days, the elimination of the morphotype II aggregates from the reactor was observed. The subsequent selection of the community was associated with the development of the morphotype I aggregates, in which the relative abundance of PAO increased significantly, resulting in higher efficiency of phosphorus removal. Metagenomic analysis revealed a predominance of the organisms closely related to Candidatus Accumulibacter IС and IIС and of Ca. Accumulibacter IIB among the PAO. Based on the content of the genes of the key metabolic pathways, the genomes of potential PAO belonging to the genera Amaricoccus, Azonexus, Thauera, Zoogloea, Pinisolibacter, and Siculibacillus were selected. The patterns of physicochemical processes and the microbiome structure associated with granule formation and succession of the microbial communities were revealed.